Can EU Act as a Democracy Promoter? Analysing the Democratization Demand and Supply in Turkey – EU Relations - Çiğdem Üstü (Romanian Journal of European Affairs)
The EU’s role to assist Turkey in its democratization efforts has been debated during Turkey’s candidacy. However, in the second decade of the 21st century, this role of the EU lost its visibility while Turkey seemed to lose its interest in reform movements. This paper, inspired by Pevehouse, defines the EU as a supplier of democratization mechanisms and Turkey as an actor in need. Although lack of enthusiasm and disengagement have come to characterize Turkey-EU relations, this study aims to demonstrate that there are differences between the governing and the opposition actors’ views on the EU and its role in the democratization of Turkey. Data collected from the speeches of opposition parties’ parliamentarians between 1 January 2011 and 31 August 2016 demonstrates the similarities observed in these parties’ concerns regarding democratic practices and the perception of the EU as an actor strengthening democracy, while indicating that the EU, as a supplier, overlooked their concerns during the process.